2015
DOI: 10.1007/s10637-015-0235-5
|View full text |Cite
|
Sign up to set email alerts
|

AZD3514, an oral selective androgen receptor down-regulator in patients with castration-resistant prostate cancer – results of two parallel first-in-human phase I studies

Abstract: AZD3514 has moderate anti-tumour activity in pts with advanced CRPC but with significant levels of nausea and vomiting. However, anti-tumour activity as judged by significant PSA declines, objective responses and durable disease stabilisations, provides the rationale for future development of SARD compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Another strategy is to pharmacologically trigger AR degradation, given the analogous success with the estrogen receptor degrader fulvestrant, used for the treatment of metastatic breast cancer progressing after failure of first-line antiestrogen therapy 114 . AZD3514, a purported AR degrader, showed PSA declines in 13% of CRPC patients but clinical development was halted due to gastrointestinal toxicity 115 .…”
Section: Future Therapeutic Options For Crpcmentioning
confidence: 99%
“…Another strategy is to pharmacologically trigger AR degradation, given the analogous success with the estrogen receptor degrader fulvestrant, used for the treatment of metastatic breast cancer progressing after failure of first-line antiestrogen therapy 114 . AZD3514, a purported AR degrader, showed PSA declines in 13% of CRPC patients but clinical development was halted due to gastrointestinal toxicity 115 .…”
Section: Future Therapeutic Options For Crpcmentioning
confidence: 99%
“…At the end of that study, no patients below 2000 mg BID had met the pre-determined DLT criteria. However moderate or greater nausea and vomiting were significant tolerability concerns and caused higher doses to be considered non-tolerable [22]. Therefore, moderate or greater (CTCAE grade 2+) nausea and vomiting was retrospectively defined as a DLT.…”
Section: Methodsmentioning
confidence: 99%
“…AZD3514, which binds the AR LBD and prevents its ligand-driven nuclear translocation, promotes down-regulation of AR levels. It has been clinically evaluated, but disappointingly only moderate anti-tumour activity in patients with advanced CRPC was observed; it was also shown to be poorly tolerated, with nausea and vomiting being the main toxicities [148] . In the 2012, Yamashita et al [149] identified that ASC-J9 (73), also named as dimethylcurcumin, functioned as an AR degradation enhancer for full length AR and AR splicing variants.…”
Section: Seviteronel (5mentioning
confidence: 99%